Reactive Oxygen and Nitrogen Species in Plants - Francisco J Corpas; José M. Palma (MDPI AG, 2024)
Reactive oxygen and nitrogen species (ROS and RNS) include two families of molecules that, in recent years, have been shown to be involved in a wide range of biological functions, such as seed and pollen germination, the development and regulation of root architecture, stomatal movement, senescence, flowering, and fruit formation and ripening [...]